(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The choice to carry out this investigation was made in response to the fact that natural aggregate (coarse and fine) that complies with Indian Standards is currently getting harder to find and more expensive because of its delayed availability caused by land use regulations, illegal dredging associated with the sand mafia, and accessibility to the river source during the rainy season. In light of this, a study was done to see what would happen if natural sand were largely replaced with stone dust in concrete. An experimental program using partial replacements of fine aggregate with stone dust at 30%, 40%, 50%, 60%, and 70% was undertaken for concrete of M25 grade with a 0.46 water cement ratio. In this investigation, sets of cubes and beams were cast for compressive.